KONTRIBUSI SISTEM INFORMASI MAJANEMEN TERHADAP EFEKTIVITAS KERJA PEGAWAI BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAH DESA PROVINSI SULAWESI TENGGARA - La Tarifu (Universitas Halu Oleo, 2018)
The purpose of this paper is to determine the contribution and influence of management information systems on the work effectiveness of employees in the Community Empowerment and Village Government Agency of Southeast Sulawesi Province.This paper examines two variables, namely the independent variable is the influence of the Management Information System system which consists of dimensions: functionalization, integration, professionalism, quality, equity, coordination, while the employee work effectiveness dependent variable consists of three dimensions each: time measurement, yield size and cost size.The research method used in this study is the explanatory survey. The population in this study were all Civil Servants at the Community Empowerment and Village Government Agency of Southeast Sulawesi Province, amounting to 93 people and a sample of 48 people representing each level of education, namely Senior High School, Bachelor / DIII, Bachelor, and Masters. The research variable is a management information system as an independent variable (X) and employee work effectiveness is the dependent variable (Y).The results of the study indicate that there is a significant influence and there is a contribution of management information systems to the work effectiveness of employees at the Community Empowerment and Village Government Agency of Southeast Sulawesi Province. The biggest influence of the variables forming the management information system is the dimension of integration, and coordination, while the smallest dimension of the variables forming the management information system is the dimension of equity. The solution that needs to be developed is improving employee competencies through education and technical training in management information systems. Keywords : Management Information System, Effectiveness of Employee's Work